Spatial Numerical Range of Operators on Weighted Hardy Spaces - Abdolaziz Abdollahi; Mohammad Taghi Heydari (International Journal of Mathematics and Mathematical Sciences)
We consider the spatial numerical range of operators on weighted Hardy spaces and give conditions for closedness of numerical range of compact operators. We also prove that the spatial numerical range of finite rank operators on weighted Hardy spaces is star shaped; though, in general, it does not need to be convex.